How can we re-program students who want to improve their oral performance in English in third semester of the modern languages program at the University of Quindío that are not pre-disposed to do so? (2016)
In a globalized world, the need to know English is growing. Moreover, for most students it is now mandatory for graduation in most careers requirements. The problem is that everyone realizes this need but not everyone can do it. Not everyone has the mindset required to learn English. This is due to the way their subconscious mind is programmed. Here is where NLP gives us the necessary tools to reprogram our minds so we change own old thoughts about learning English. The main tool used in this project is called reframing, so named for its creators (Grinder and Blander) in the 70s, which Bandler and Grinder did was studying Virginia Satir: a family therapist, Fritz Perls: Psychotherapist , and Milton Erikson: Hypnotherapist, and describe precisely what they did to achieve those outstanding results.